Endothelial dysfunction, abnormal vascular structure and lower urinary tract symptoms in men and women. (15th June 2018) - Matsui, Shogo; Kajikawa, Masato; Maruhashi, Tatsuya; Iwamoto, Yumiko; Oda, Nozomu; Kishimoto, Shinji; Hashimoto, Haruki; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Hida, Eisuke; Goto, Chikara; et al.
Abstract: Background: Lower urinary tract symptoms (LUTS) is not only common symptoms in elderly men and women but also risk of future cardiovascular events. The purpose of this study was to evaluate the relationships of vascular function and structure with LUTS in men and women. Methods: We investigated flow-mediated vasodilation (FMD) and nitroglycerine-induced vasodilation (NID) as vascular function, brachial-ankle pulse wave velocity (baPWV) as vascular structure, and LUTS assessed by International Prostate Symptom Score (IPSS) in 287 men and 147 women. Results: IPSS was significantly correlated with traditional cardiovascular risk factors, Framingham risk score, FMD, NID and baPWV. Moderate to severe LUTS was associated with the prevalence of coronary heart disease in men but not in women. In men, FMD and NID were significantly lower in the moderate to severe LUTS group than in the none to mild LUTS group (2.1 ± 2.0% vs. 4.0 ± 3.0% and 9.3 ± 6.1% vs. 12.8 ± 6.6%, P  < 0.001, respectively). baPWV was significantly higher in the moderate to severe LUTS group than in the none to mild LUTS group (1722 ± 386 cm/s vs. 1509 ± 309 cm/s, P  < 0.001). In multivariate analysis, FMD was independently associated with a decrease in the odds ratio of moderate to severe LUTS in men (OR: 0.83, 95% CI, 0.72–0.95; P  = 0.008) but not in women. NID and baPWV were not independently associated with moderate to severe LUTS either in men or women. Conclusions: These findings suggest that endothelial dysfunction is associated with LUTS in men. LUTS in men may be useful for a predictor of cardiovascular events. Clinical trial registration information: URL for Clinical Trial:http://UMIN ; Registration Number for Clinical Trial: UMIN000003409. Highlights: Endothelial dysfunction was associated with LUTS in men. Moderate to severe LUTS was associated with the prevalence of coronary heart disease in men. LUTS in men should be focused as the phenotype of atherosclerosis.